The Effect of Prophet Yusuf Storytelling on Students' Grammar Mastery - Rianto Rianto; Febria Sri Artika; Loli Safitri (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
The study of grammar has been shifting in language teaching classroom. However, the fact that the difficulty to understand grammar, especially past tense among the junior high school students has been an issue that needs to be solved. This study investigated the effect of using storytelling of Prophet Yusuf based on Quran verses towards students’ grammar mastery at the 8th grade in MTsS Diniyyah Pasia, Agam, West Sumatera. This quasi-experimental research involved 32 sample students who were treated as experimental class and taught by using storytelling of Prophet Yusuf and another 32 students as control class who were taught by using conventional technique. These two groups of samples were determined by using purposive sampling technique. To analyze the data from the students’ grammar test of pretest and posttest of experimental and control classes, the researcher used SPSS program.  The result of the post-test scores of both classes, experimental and control classes, showed that the t-obtained (3.557) was bigger than t table (1.67). It indicates that the use of Prophet Yusuf Storytelling which is based on Quran verses in learning Grammar can help the students to master the grammatical pattern effectively.